Hedging devices in Slovene-English Translation: A Corpus-Based Study - Pisanski Peterlin, Agnes (Nordic Journal of English Studies, 2010)
Translating research articles into English is fairly common practice in certain disciplines; however, the translated articles are generally not perceived as translations by the reader. Consequently, the translation of the research article is often invisible. Relatively little data is available on issues arising in this type of translation. The present paper aims to explore one of the issues which arise in translating research articles, namely, the question how hedging devices are translated. The importance of hedging in academic discourse has been established by a number of studies; in addition, considerable cross-cultural variation has been observed in the use of hedging. This raises the question of the effect of this variation on translation. In order to explore this question, a corpus of 90 research articles in geography—30 original Slovene articles, 30 English translations of Slovene articles and 30 comparable original English articles—is analysed. The frequency and form of hedging devices used in translated and original English texts are compared in order to identify the ways in which Slovene-English translations differ from comparable English language originals. The results show considerable differences between the two comparable corpora: only half as many hedging devices are used in the translated texts as in the originals and the variety of hedging devices is considerably more limited in the translations.